Implementasi Kompetensi Profesionalisme Guru dalam Pengembangan Kinerja Pembelajaran - J, Hasnawati (Universitas Islam Negeri Alauddin Makassar, 2016)
The tasks of the teacher as a profession are to educate, to teach, and to train. Educating means to continue and develop the values of life; teaching means to continue and develop the science; training means to develop skills for the learners’ lives. To be able to carry out the duties and responsibilities stated previously, teachers are demanded to have some specific skills and competencies as part of their professionalism. Professional competence is the ability to master the learning materials broadly and deeply. In Islamic education concept, it deals with the teachers’ ability to carry out their duties in a professional manner based on the teachings of Islam. Teacher professional competence refers to the ability of a teacher to conduct their profession well. It deals with the Law of the Republic of Indonesia Number 14 Year 2005 about teachers and lecturers as covered in Chapter III Article 7 regulating about the principles of professionalism.